2019
DOI: 10.1103/physrevb.100.220409
|View full text |Cite
|
Sign up to set email alerts
|

Comparing all-optical switching in synthetic-ferrimagnetic multilayers and alloys

Abstract: We present an experimental and theoretical investigation of all-optical switching by single femtosecond laser pulses. Our experimental results demonstrate that, unlike rare earth-transition metal ferrimagnetic alloys, Pt/Co/[Ni/Co] N /Gd can be switched in the absence of a magnetization compensation temperature, indicative for strikingly different switching conditions. In order to understand the underlying mechanism, we model the laser-induced magnetization dynamics in Co/Gd bilayers and GdCo alloys on an equa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 25 publications
6
95
0
Order By: Relevance
“…The key difference between MRG and GdFeCo is that while the latter exhibits SP-AOS when measured within about 100 K either above or below its compensation point 11,30 , MRG only switches when the initial temperature is below T comp . Therefore, initially, the angular momentum of the 4c sublattice must be higher than that of 4a to switch successfully.…”
Section: Resultsmentioning
confidence: 99%
“…The key difference between MRG and GdFeCo is that while the latter exhibits SP-AOS when measured within about 100 K either above or below its compensation point 11,30 , MRG only switches when the initial temperature is below T comp . Therefore, initially, the angular momentum of the 4c sublattice must be higher than that of 4a to switch successfully.…”
Section: Resultsmentioning
confidence: 99%
“…All optical switching (AOS) of magnetization using ultrashort laser pulses, whether it is helicity dependent [1][2][3][4][5][6] or helicity independent (AO-HIS), [4,[6][7][8][9][10][11][12] exhibits a very interesting out of equilibrium physics as well as promising practical implications. [13] Many attempts to unveil the detailed mechanism of those phenomena have been carried out both theoretically [8,[14][15][16][17][18][19][20][21][22][23][24] and DOI: 10.1002/advs.202001996 experimentally. [1][2][3][4][5][6][7][8][9][10][11][12][25][26][27][28] AO-HIS is observed after a single femtosecond laser pulse and most of the materials showing this effect are gadolinium-based rare earth (RE)/transition metals (TMs) ferrimagnets.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][25][26][27][28] AO-HIS is observed after a single femtosecond laser pulse and most of the materials showing this effect are gadolinium-based rare earth (RE)/transition metals (TMs) ferrimagnets. [24] AO-HIS has been extensively studied in amorphous GdFeCo alloy. [10] It was shown that AO-HIS could only be observed for a limited range of alloy concentration, laser fluence and pulse duration.…”
Section: Introductionmentioning
confidence: 99%
“…It is important during this entire process that both S 4a and S 4c do not simultaneously fall to a level where thermal spin correlations can dominate, leading to loss of magnetic memory and subsequent random behavior. This situation is encountered if the net incident fluence [21,55] is excessive, giving rise to the spatially inhomogeneous pattern shown in Supplemental Fig. S2.…”
mentioning
confidence: 99%